Introduction to law & paralegal studies - Scuderi, Connie Farrell (McGraw-Hill, 2008)
Scuderis Introduction to Law & Paralegal Studies teaches the basic skills paralegals will nee when working in the field using practical, uncomplicated approach. The material is directly applicable, providing an accurate sense of what paralegals do. The text provides basic coverage of the topics most important for a beginning paralegal student.